Azerbaijan Republic : Staff Report for the 2004 Article IV Consultation, Fourth Review Under the Poverty Reduction and Growth Facility, Requests for Waiver of Performance Criteria, Extension of Arrangement, Reduced Access and Rephasing of Disbursements. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines Azerbaijan Republic's 2004 Article IV Consultation and Fourth Review Under the Poverty Reduction and Growth Facility. A long-term oil revenue management strategy has been adopted by the authorities, targeting a path of non-oil deficits over the medium term that seeks to preserve macroeconomic stability and also avoid overstretching implementation capacity. To ensure coherent fiscal policy, annual budgets will need to start from the poverty reduction strategy and incorporate public investment and regional development programs.